2022
DOI: 10.1186/s12882-022-02776-w
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider perspectives on integrating peer support in non-dialysis-dependent chronic kidney disease care: a mixed methods study

Abstract: Background Peer support complements traditional models of chronic kidney disease (CKD) care through sharing of peer experiences, pragmatic advice, and resources to enhance chronic kidney disease self-management and decision-making. As peer support is variably offered and integrated into multi-disciplinary CKD care, we aimed to characterize healthcare providers’ experiences and views on peer support provision for people with non-dialysis-dependent CKD within Canada. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In contrast, few multidisciplinary CKD clinics embed peer support within their care programs. 34 Patients with advanced, non-dialysis CKD often lack overt manifestations yet face challenges related to high symptom burden, metabolic complications, and difficult treatment-related decisions (e.g., choosing among dialysis types). 35 Thus, our findings endorse an inclusive but tailored approach to peer support that purposefully addresses CKD-specific support gaps and connects individuals within the broader kidney community.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, few multidisciplinary CKD clinics embed peer support within their care programs. 34 Patients with advanced, non-dialysis CKD often lack overt manifestations yet face challenges related to high symptom burden, metabolic complications, and difficult treatment-related decisions (e.g., choosing among dialysis types). 35 Thus, our findings endorse an inclusive but tailored approach to peer support that purposefully addresses CKD-specific support gaps and connects individuals within the broader kidney community.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to financial benefits, previous studies have noted that peer support groups allow sharing of experiences, advice on self-management and decision-making. 30 Similarly, other scholars have described peer support as an effective educational method for patients. 31 We found that screening for KD required multi-disciplinary input.…”
Section: Facilitators Of Kd Screeningmentioning
confidence: 99%